ТHE CONDITION STATE MECHANISMS PLANNING OF AREAS - Bezzubko B.I. (Pressing Problems of Public Administration, 2015)
In the article analyzes the problems in the implementation of the state policy in the development of territories. Classification was carried out of the existing approaches in the development of strategic documents at local and regional levels (management approach , expert approach, public approach).